2014
DOI: 10.1007/s10339-014-0636-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathologies in functional connectivity, feedback control and robustness: a global workspace perspective on autism spectrum disorders

Abstract: We study the background to problems of functional connectivity in autism spectrum disorders within the neurocognitive framework of the global workspace model. This we proceed to do by observing network irregularities detracting from that of a well-formed small world network architecture. This is discussed in terms of pathologies in functional connectivity and lack of central coherence disrupting inter-network communication thus impairing effective cognitive action. A typical coherence-connectivity measure as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…A later fMRI study of the EFT found not only reduced activation of the same visuospatial network, but also reduced connectivity between frontal areas and visuospatial areas (Damarla et al, 2010). A consistent finding in neuroimaging work in ASD research is indeed changes in connectivity, with many studies showing reduced long range connectivity in individuals with ASD (Glazebrook and Wallace, 2015; Kikuchi et al, 2015). This further supports the role of connectivity in atypical perceptual processing in ASD.…”
Section: Theories Of Altered Sensory and Cognitive Functioning In Asdsupporting
confidence: 52%
“…A later fMRI study of the EFT found not only reduced activation of the same visuospatial network, but also reduced connectivity between frontal areas and visuospatial areas (Damarla et al, 2010). A consistent finding in neuroimaging work in ASD research is indeed changes in connectivity, with many studies showing reduced long range connectivity in individuals with ASD (Glazebrook and Wallace, 2015; Kikuchi et al, 2015). This further supports the role of connectivity in atypical perceptual processing in ASD.…”
Section: Theories Of Altered Sensory and Cognitive Functioning In Asdsupporting
confidence: 52%
“…Specifically, high clustering coefficients suggest overconnectivity, which may not be functional. Instead, this pattern of overconnectivity may result in diffuse processing and recruitment of nonspecialized neural mechanisms (Glazebrook & Wallace, 2015). The increased energetic cost required to transmit signals across a diffuse processing system may in turn decrease efficiency of processing (Bullmore & Sporns, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Glazebrook and Wallace ( 2014 ), associate lesions to global connectivity with autism spectrum disorders. It is highly intriguing that some autism spectrum patients appear to share some of the characteristics with Kim Peek (and some other split-brain patients), even though clearly not autistic, including an seeming inability to deal with non-literal speech, prodigious attention to detail, and savant syndrome.…”
Section: Dynamical Representationsmentioning
confidence: 99%
“…The hubs and their interconnections may qualify as the architecture of the global workspace, whereas the modules they connect can be regarded as their client systems (see also Glazebrook and Wallace, 2014 for a similar proposal).…”
Section: Dynamical Representationsmentioning
confidence: 99%